2012
DOI: 10.1074/jbc.m111.252742
|View full text |Cite
|
Sign up to set email alerts
|

Loading-related Regulation of Transcription Factor EGR2/Krox-20 in Bone Cells Is ERK1/2 Protein-mediated and Prostaglandin, Wnt Signaling Pathway-, and Insulin-like Growth Factor-I Axis-dependent

Abstract: Of the 1,328 genes revealed by microarray to be differentially regulated by disuse, or at 8 h following a single short period of osteogenic loading of the mouse tibia, analysis by predicting associated transcription factors from annotated affinities revealed the transcription factor EGR2/Krox-20 as being more closely associated with more pathways and functions than any other. Real time quantitative PCR confirmed up-regulation of Egr2 mRNA expression by loading of the tibia in vivo. In vitro studies where strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 62 publications
4
40
0
Order By: Relevance
“…EGR2 expression in bone is strongly induced by loading, and its expression in cultured osteoblastic cells is also increased by strain (36). Moreover, major signaling pathways associated with loading and bone formation, such as prostaglandins, IGF-I, and Wnt3a, also rapidly increase EGR2 expression in osteoblasts (36). In contrast, glucocorticoid treatment leads to a drastic decrease in bone marrow osteoprogenitor number and an increase in osteoblast and osteocyte apoptosis in mice (2).…”
Section: Discussionmentioning
confidence: 99%
“…EGR2 expression in bone is strongly induced by loading, and its expression in cultured osteoblastic cells is also increased by strain (36). Moreover, major signaling pathways associated with loading and bone formation, such as prostaglandins, IGF-I, and Wnt3a, also rapidly increase EGR2 expression in osteoblasts (36). In contrast, glucocorticoid treatment leads to a drastic decrease in bone marrow osteoprogenitor number and an increase in osteoblast and osteocyte apoptosis in mice (2).…”
Section: Discussionmentioning
confidence: 99%
“…Egr1 also appears to be important in regulating the inflammatory response after injury (46). Both Egr1 and Egr2 can respond to a number of different types of stimuli including mechanical stimulation, wounding, and growth factors (2,13,16,32,46,48). A PASTAA (Predicting Associated Transcription factors from Annotated Affinities) analysis has shown that Egr2 appears more often in loading-related functions in bone than any other gene (48).…”
Section: Discussionmentioning
confidence: 99%
“…Both Egr1 and Egr2 can respond to a number of different types of stimuli including mechanical stimulation, wounding, and growth factors (2,13,16,32,46,48). A PASTAA (Predicting Associated Transcription factors from Annotated Affinities) analysis has shown that Egr2 appears more often in loading-related functions in bone than any other gene (48). Downstream targets for Egr1 and Egr2 include mediators of inflammation, coagulation, and different growth factors (2,16,46), and the gene expression for Egr1 and Egr2 can be induced by a number of different signaling pathways depending on which primary stimulus is involved (33).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 3 genes, Arc, Egr2 and Hspa1b, functionally involved in 'behavior', were also expected to participate in 'blood pressure' control, as well as in the development of ADHD. Arc plays a critical role in the consolidation of enduring synaptic plasticity and memory storage (28), while Egr2 encodes a transcription factor with 3 tandem C2H2-type zinc fingers [since defects in this gene are associated with neurological diseases, such as Charcot-Marie-Tooth disease and Dejerine-Sottas syndrome, it has been suggested to play a role in learning and long-term potentiation (29,30)]. Hspa1b encodes a 70-kDa heat-shock protein, which is known to promote neurodegeneration in sporadic Parkinson's disease through its functional interaction with other Parkinson's disease-related genes (31).…”
Section: G-4)mentioning
confidence: 99%